Funeral of South African struggle stalwart Moses Mabhida in Maputo. F.l.t.r. (in front): Slovo, Tambo, Machel - Brown, David
Funeral of South African struggle stalwart Moses Mabhida in Maputo. F.l.t.r. (in front): Slovo, Tambo, Machel.